2015
DOI: 10.1080/10911359.2014.966221
|View full text |Cite
|
Sign up to set email alerts
|

Registration, Residency Restrictions, and Community Notification: A Social Capital Perspective on the Isolation of Registered Sex Offenders in Our Communities

Abstract: This article highlights the importance of social capital for registered sex offenders who are reintegrating back into their communities. Although not always identified among community corrections, the sex offender registry creates a punitive atmosphere that diminishes the amount of available social capital for all involved-community members, sex offenders, and the government. Lost social capital contributes to recidivism, reentry problems, and mental health issues among registered sex offenders. We argue that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In a similar way, excessive shame from being associated with the registry or from having a loved one on the registry can lead to disintegrative shame (Braithwaite, 1989), which hinders offenders’ reintegration into society and increases stress triggers associated with recidivism (Petersilia, 2003; Tewksbury, 2005). Although prior research examines the existence of social isolation and shame as emotional unintended consequences of the sex offender registry (Bailey & Sample, 2017; Edwards & Hensley, 2001; Farkas & Miller, 2007; Tewksbury, 2005; Tewksbury & Lees, 2006; Tolson & Klein, 2015), to date, there have been no systematic examinations in the variation and predictors of these two consequences. The current study attempted to fill that gap by examining variations of social isolation and shame for registered sex offenders and their FMs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a similar way, excessive shame from being associated with the registry or from having a loved one on the registry can lead to disintegrative shame (Braithwaite, 1989), which hinders offenders’ reintegration into society and increases stress triggers associated with recidivism (Petersilia, 2003; Tewksbury, 2005). Although prior research examines the existence of social isolation and shame as emotional unintended consequences of the sex offender registry (Bailey & Sample, 2017; Edwards & Hensley, 2001; Farkas & Miller, 2007; Tewksbury, 2005; Tewksbury & Lees, 2006; Tolson & Klein, 2015), to date, there have been no systematic examinations in the variation and predictors of these two consequences. The current study attempted to fill that gap by examining variations of social isolation and shame for registered sex offenders and their FMs.…”
Section: Discussionmentioning
confidence: 99%
“…Sex offender FMs are also potentially affected by these unintended consequences, depending on how closely the FMs are associated with their registrant loved one (Farkas & Miller, 2007). Scholars find that sex offender FMs experience similar unintended consequences of SORN laws including housing and employment difficulties, public harassment, and high levels of stress (Bailey & Sample, 2017; Farkas & Miller, 2007; Levenson & Tewksbury, 2009; Tewksbury & Levenson, 2009; Tolson & Klein, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously discussed, the legislation of the early 1990s was mandated as a way to control and supervise sex offenders while increasing community member awareness of the whereabouts of sex offenders postconviction. These laws are associated with unintended consequences, and researchers have consistently documented that RSOs have problems with unemployment (Klein, Tolson, & Collins, 2014; Tewksbury, 2004, 2005; Tolson & Klein, 2015); finding permanent, suitable housing (Chajewski & Mercado, 2008; Levenson & D’Amora, 2007; Tewksbury, 2007; Zgoba, Levenson, & McKee, 2009); and experience verbal or physical harassment from community members (Tewksbury & Lees, 2006) as a result of SORN laws. These laws were meant to provide formal and informal social controls over RSOs to reduce recidivism while providing protection for community members, but research has suggested that the opposite has occurred.…”
Section: Introductionmentioning
confidence: 99%